2009
DOI: 10.1071/rd09004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary manipulation of Bos indicus × heifers during gestation affects the reproductive development of their heifer calves

Abstract: The effect of nutrition during the first and second trimesters of pregnancy in composite beef heifers on reproductive parameters of their female calves was determined in the present study. At artificial insemination, heifers were assigned to one of four treatment groups (i.e. HH, HL, LowH and LL) depending on the level of crude protein intake (H = high; L = low) for first and second trimesters of pregnancy. Gonadotrophin concentrations and ovarian parameters were measured in their female calves at 5 and 23 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 46 publications
1
46
2
Order By: Relevance
“…Similar to sheep, prenatal maternal nutrition did not affect the onset of puberty in beef cattle (Martin et al 2007;Sullivan et al 2009;Mossa et al 2013), but higher offspring pregnancy rates were observed following protein supplementation in late pregnancy (Martin et al 2007) and when the AFC before breeding was high (Cushman et al 2009). In contrast, manipulation of the post-weaning diet in beef heifers did not affect AFC or overall pregnancy rate (Eborn et al 2013).…”
Section: Female Offspring: Cattlementioning
confidence: 88%
See 1 more Smart Citation
“…Similar to sheep, prenatal maternal nutrition did not affect the onset of puberty in beef cattle (Martin et al 2007;Sullivan et al 2009;Mossa et al 2013), but higher offspring pregnancy rates were observed following protein supplementation in late pregnancy (Martin et al 2007) and when the AFC before breeding was high (Cushman et al 2009). In contrast, manipulation of the post-weaning diet in beef heifers did not affect AFC or overall pregnancy rate (Eborn et al 2013).…”
Section: Female Offspring: Cattlementioning
confidence: 88%
“…Thus, birthweight (as a proxy for fetal nutrient supply) was positively associated with the antral follicle count (AFC) in a large population of neonatal beef calves that died due to dystocia, and in adult heifers examined by ultrasound (Cushman et al 2009). Reduced ovarian weight and large follicle diameter at 30 months is reported following slow prenatal growth rates (Wilkins et al 2006), whereas a general reduction in all follicle types was evident following exposure to a low-then highprotein diet during the first two-thirds of gestation (Sullivan et al 2009). A direct effect of maternal undernutrition during the first third of gestation on the ovarian follicle reserve has been documented using serial ultrasound (five occasions) during prepubertal and adult life (Mossa et al 2013).…”
Section: Female Offspring: Cattlementioning
confidence: 99%
“…Freetly et al (2005) reported that nutrient intake could be limited for pregnant cows during the second trimester without altering the subsequent reproductive performance of the cows. However, maternal nutrient status during pregnancy may also affect the lifetime productivity of the female offspring, because there is evidence that both nutrient restriction and nutrient excess during pregnancy may negatively impact the ovarian reserve of the subsequent generation (Da Silva et al, 2002Ireland et al, 2011;Sullivan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, resulting progeny of undernourished animals have reduced birth weight and often express poor postnatal growth rates (Greenwood et al 2000, Ford et al 2007, increased morbidity (Garite et al 2004), increased proportion of body fat in relation to lean (Greenwood et al 2000, Ford et al 2007) metabolic disorders (Fowden et al 2005, Ford et al 2007, and alterations in organ function (Da Silva et al 2002, Sullivan et al 2009, Echternkamp et al 2012.…”
Section: Developmental Programmingmentioning
confidence: 99%